Upaya Pekerja Seks Komersial Lokalisasi Daerah Pesisir dan Perbatasan dalam Mencegah Penularan HIV AIDS: Studi Fenomenologi - Dewy Haryanti Parman; Agung Waluyo; Sri Yona; Bambang Wispriyono (Universitas Faletehan, 2024)
HIV AIDS cases continue to increase every year. In 2023, out of 1,414 HIV AIDS cases in North Kalimantan, Indonesia, 500 cases were in Tarakan region. This study aimed to reveal the situation of the extent of efforts of commercial sex workers (CSWs) in preventing HIV AIDS transmission in coastal and border areas of Tarakan. This research was qualitative with a descriptive phenomenological approach. This study involved 15 CSWs in the localization of Tarakan area as the participants. The data analysis used thematic analysis by Braun and Clarke. This study produced four themes, namely: (1) health checks were carried out on an irregular basis, (2) customers who refused to use condoms were still served, (3) the use of antibiotics to prevent HIV AIDS transmission, and (4) limiting customers. The prevention of HIV AIDS transmission by CSWs had not been maximized due to the limitations of economic background and negotiation skills and a lack of understanding of HIV AIDS. A more comprehensive educational approach was needed to raise awareness of the importance of self-prevention from infectious diseases to work, so that they can work for a long time.